PEDAGOGICAL ERUDITION AS A FACTOR IN THE DEVELOPMENT OF THE THINKING CULTURE OF FUTURE PRIMARY SCHOOL TEACHERS (Universal International Scientific Journal, 2026)
This article examines the development of a culture of thinking in future primary school teachers within the system of higher pedagogical education. It substantiates the importance of pedagogical erudition as a key factor in shaping the intellectual culture and professional thinking of future teachers. Theoretical approaches to understanding culture of thinking and pedagogical erudition are analyzed, revealing their interrelationship in the context of teacher training. Particular attention is paid to the ideas of L.S. Vygotsky's cultural-historical theory of thinking development, according to which intellectual abilities are formed through social interaction and the assimilation of cultural tools. Pedagogical conditions for developing a culture of thinking in students majoring in pedagogical training are identified, including the integration of scientific knowledge, the use of problem-based learning, and the development of research activities.
Keywords: pedagogical erudition, culture of thinking, future primary school teacher, professional thinking, pedagogical education, intellectual culture, cultural-historical theory